(untitled) (Bangladesh Journal of Pharmacology, 2013)
In this present study, we computationally identified the germline missense mutation in the E-cadherin (CDH1) gene causing hereditary diffuse gastric cancer (HDGC). The analysis was initiated with SIFT followed by PolyPhen and I-Mutant2.0 programs with the help of 68 CDH1 variants retrieved from dbSNP. The analysis indicates that 10 variants such as P201R, A298T, E336D, C695R, N751K, Y755C, D768N, G879S, D882N and R169H were commonly found to be less stable and damaging by SIFT, PolyPhen and I-Mutant2.0 programs. Furthermore, SNPs&GO was used to predict the disease related mutations from the protein sequence. Finally, the affinities for the cetuximab with CDH1 variants were examined by using molecular docking algorithm. The result showed that P201R, A298T, E336D and R169H variants were found to be highly significant than the other mutations considered in our analysis. We sincerely hope that these findings certainly helpful for the experimental biologist working in HDGC drug development.